2020
DOI: 10.3389/fmats.2020.00287
|View full text |Cite
|
Sign up to set email alerts
|

The BCC-FCC Phase Transformation Pathways and Crystal Orientation Relationships in Dual Phase Materials From Al-(Co)-Cr-Fe-Ni Alloys

Abstract: The alloy system Al-(Co)-Cr-Fe-Ni contains compositional ranges where a solid state BCC-FCC phase transformation leads to dual-phase materials composed of facecentered cubic (FCC) and body-centered cubic (BCC) phases with nearly equal volume fraction. The microstructure arising from this transformation at slow cooling rates is the classical Widmanstätten structure, with FCC-laths and colonies growing from grain boundaries into the parent BCC-B2 grain. Very distinct microstructures are obtained, when Widmanstät… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…First of all, there is a good agreement between nominal and chemical composition of the alloy in as-received state confirming the consistency of semi-quantitative EDX measurements. In the as-received powder, there is minor elemental segregation across the powder particle in Figure 3 a, whilst the detailed SEM image in Figure 3 b shows fine alternating layers which have some similarity to the morphology formed via spinodal reaction in Al–(Co)–Cr–Fe–Ni HEA [ 18 ]. Further analysis on the chemical composition of the alternating layers is needed to clarify the reaction for the formation of the phases.…”
Section: Resultsmentioning
confidence: 99%
“…First of all, there is a good agreement between nominal and chemical composition of the alloy in as-received state confirming the consistency of semi-quantitative EDX measurements. In the as-received powder, there is minor elemental segregation across the powder particle in Figure 3 a, whilst the detailed SEM image in Figure 3 b shows fine alternating layers which have some similarity to the morphology formed via spinodal reaction in Al–(Co)–Cr–Fe–Ni HEA [ 18 ]. Further analysis on the chemical composition of the alternating layers is needed to clarify the reaction for the formation of the phases.…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent study on this microstructure using detailed EBSD analysis revealed that this microstructure is not a result of eutectic reaction but a result of solid state decomposition of parent BCC grains into FCC and BCC [21]. This solid state decomposition leading to a Widmanstatten pattern of FCC lamellae in BCC matrix was accepted by other research groups [22]. Further, this alloy has stable intermetallic phases at lower temperatures which provides an opportunity to investigate the transformation pathways involved in forming the intermetallics in FCC and BCC based phases.…”
mentioning
confidence: 84%
“…Moreover, with the increase in aluminum content, the A1 field overlaps part of the miscibility gap, creating a region where the three phases can coexist at equilibrium. This combination of phases yields the possibility to obtain a large variety of microstructure morphologies, finely controlled by the alloy composition and the processing route [4].…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%
“…As-cast Al n CrFe 2 Ni 2 alloys with composition n % 1 have shown exceptional tensile strength and ductility [2,5]. These properties have been attributed to the peculiar dual-phase microstructure consisting of A1 and B2 regions, formed simultaneously with the decomposition in the B2 phase [4]. Furthermore, the use of additive manufacturing techniques, such as laser powder bed fusion [6] and laser metal deposition [7], has revealed a strong dependency of the phase fractions and morphology on the cooling conditions.…”
Section: Graphical Abstract Introductionmentioning
confidence: 99%